On the difference in the rise times of the two SES electric field components - Varotsos, Panayiotis A. (Proc Jpn Acad Ser B Phys Biol Sci, 2004)
The study of low frequency signal transmission in conductive media, reveals that the electric and magnetic fields follow diffusion type equations. In a previous paper (Varotsos et al.1)) experimental evidence was forwarded that for epicentral distances of the order of 100 km, the SES electric field variations precede those of the magnetic ones by a time of the order of 1 sec. In the present paper, we present evidence that this peculiarity still pertains (but to a smaller extent), when studying the differences in the components of the electric field. This cannot be probably observed in the scale of laboratory measurements, lying usually within the error bars of the current experimental facilities. A tentative theoretical justification, termed as τ-approximation, is presented which accounts for the measurements of electric field components. The present findings can provide a unique tool for the discrimination between remote and nearby sources by using data from electric measurements alone.